ASPEK KESADARAN HUKUM MASYARAKAT DI KELURAHAN CIPONDOH TERHADAP PELAKSANAAN KELURAHAN BERSIH NARKOBA - Tedy Subrata; Muchin Mansyur; Hendrik Fasco Siregar; Letkol Purn Sugino; Dadang Dadang (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
GROUP 13 IMPLEMENTATION OF TRI DHARMA HIGH SCHOOL OF LEGAL SCIENCES PAINAN CIKUPA REGENCY TANGERANG REGENCY, BANTEN PROVINCE SERVICE TO THE COMMUNITY "ASPECTS OF COMMUNITY LEGAL AWARENESS IN THE CIPONDOH SUB-DISTRICT" considering that Tangerang City is in the red zone for drug trafficking and abuse in 2021 and is ranked first. Drug abuse among the younger generation is currently increasing. Worg Drugs Repot United Nation Office Drugs And Crime (UNDODC) states that in 2010 there were 153-300 million (3.4 - 6.6%) drug users in 2021 among Indonesian youth aged < 15 - > 20 years of age 4.3% have used drugs and 2.9% have used within one year and 2.5% have used in the last month efforts to prevent and eradicate drug abuse, one of which is through awareness, socialization, legal discussion about the dangers of narcotics if consumed by many people, especially for the next generation of the nation in the Cipondoh area, Tangerang City. Based on data from the Tangerang City National Narcotics Agency that the distribution and abuse of drugs covers the areas of Benda Village, Tangerang City, Karawaci, Ciledug, and Cipondoh, the Tangerang City Government through KESBANGPOL said to contribute by establishing 24 free villages from drugs in each Rukun Warga in order to Breaking the chain of drug distribution also involves community participation through the Neighborhood Association. Drug abuse from year to year shows an increasing trend, even drug abuse around the world has never been reduced and it is proven that drugs can damage the nation's future, including in the Republic of Indonesia. Banten Province is included in 14 areas prone to drug abuse and distribution, facilities and infrastructure for the implementation of rehabilitation are not yet fully available, and information dissemination on the dangers of drugs is not optimal. This Community Service aims to identify and analyze the appropriate strategy carried out by the City National Narcotics Agency. Tangerang in an effort to prevent and eradicate drug abuse, the theory used is The Four Pillar Drugs Strategy adopted from the New Mental Healt Connection. Results of the Final Report on the Tri Dharma STIH PAINAN Cikupa Program Activities, Tangerang Regency, Banten Province towards Community Service, Cipondoh Village, Tangerang City and surrounding areas , shows that the strategy of the Tangerang City National Narcotics Agency in efforts to prevent, eradicate and abuse drugs is still not optimal, the right strategy to be applied is to strengthen cooperation with all parties to jointly carry out advocacy and dissemination of adequate information, strengthen communication skills, increase capacity medical and social rehabilitation services, make efforts to reduce the impact of drug use and illicit trafficking and carry out law enforcement efforts in accordance with Law Number ; 35 of 2009, concerning Narcotics.